Guidelines for Management of Oral Dryness (Xerostomia) in the Elderly: A 2 Cases Report - Yookhum, Nathita (Srinagarind Medical Journal, 2022)
Background and Objective: Oral dryness in the elderly was often found and caused by various combination factors. The purpose of this study was to study how to take care for oral dryness in the elderly patients that affected from chronic disease, radiation therapy, and medication. Methods: This study performed in 2 cases of patients with oral dryness. Case 1, 65 years-old Thai male patient with oral dryness that came for an appointment for follow-up 1 month after receiving radiotherapy (in December 2021). This case had a congenital disease with Type 2 diabetes and intraoral examination was diagnosed with severe dryness. Provide treatment and follow-up of treatment until 3 months. Case 2, 64year-old Thai woman, was referred for treatment and follow-up due to dry mouth in 2021. The patient had congenital disease with hypertension and type 2 diabetes and Intraoral examination was diagnosed with moderate dryness. Provide treatment and follow-up of treatment until 3 months. Both patients used Clinical oral dryness score (CODS) for diagnosis. Results: Patient 1, after 3 months of treatment, the patient felt the mouth was moister, less soreness in the mouth, easier to swallow, the CODS score was decreased from 7 to 5, so pilocarpine was reduced to 5-10 mg once a day with oral moisturizing Jelly. Make an appointment for an oral health examination and fluoride coating once a month until the 6th month after treatment and follow-up. It was found that the patient felt that mouth was moister. In the oral examination, there was an increase in saliva. There is no burning sensation in the mouth at all, easier to swallow, and eat more. Patient 2, after 3 months of treatment, the patient felt that the mouth was moister, no burning sensation in the mouth, easier to swallowed, wake up less late at night. The oral examination found moist tissue, saliva was relatively clear, the CODS score decreased from 4 to 2 points. Due to the patient's had good oral condition, the oral examination was planned and fluoride coating every 6 months. Conclusion: The results of the treatment and care guidelines for dry mouth treatment in both elderly patients showed that patients were improvement in symptoms. The patient felt that the mouth was moister, no burning sensation in the mouth, easier to swallowed, eat more, and decreased CODS scores.